Community Service Practice in Teaching English as a Foreign Language in Thailand: The Experience of an Indonesian Pre-Service Teacher at Ban Huai Pao Nuea School, Loei.School - Muhammad Dava Hidayatullah; Waslurachim Safitri; Ririn Putri Ananda (Gayaku Publisher, 2026)
This community service activity aims to describe the practice of teaching English as a Foreign Language (EFL) conducted by an Indonesian pre-service teacher in a rural primary school in Thailand. EFL instruction in this context faces several challenges, including limited exposure to English, teacher-centered classroom culture, and students’ low confidence in oral communication. This activity employed a descriptive qualitative approach, with data collected through classroom observations and reflective documentation during the teaching process at Ban Huai Pao Nuea School. The findings indicate that instructional adaptations, such as simplifying learning materials, utilizing visual media, and implementing interactive and contextual activities, contributed to increased student engagement in English learning. In addition, the community service program provided meaningful professional learning experiences for the pre-service teacher in developing pedagogical, reflective, and intercultural communication competencies. These findings highlight that community service-based teaching practices can positively support EFL learning in resource-limited rural primary school contexts.